Two unreported modes of interlocking nail failure: breakout and screw bending - Suber, J. T.; Basinger, R. R.; Keller, W. G. (Veterinary and Comparative Orthopaedics and Traumatology, 2002)
Interlocking nails (ILN) have been successfully used to repair fractures of the humerus, femur, and tibia in dogs and cats. The purpose of these case reports is to describe two previously unreported complications of ILN use that occurred in three skeletally immature large breed dogs. Two cases of breakout of the ILN, through previously intact corticocancellous bone and one case of screw bending through the nail, resulted in loss of reduction and stability requiring additional surgery. Stability of the ILN construct depends upon proper placement of the ILN within the main fracture fragments, maximal medullary canal filling, and adequate nail and screw strength. In these cases, technical errors with ILN placement, relatively soft metaphyseal bone, as well as deficiencies in the ILN system may have factored into these failures.
Keywords: Interlocking nails; fixation failure